Predicting the exchange rate in Sudan using neural networks models during the period (1960 - 2017) - Adam, Fathi Ahmed Ali; Gamal El-Din, Mahmoud Mohamed Abdel Aziz; Mohammed, Adel Abdalla Adam (Journal of Economic, Administrative and Legal Sciences, 2020)
The study examined the use of artificial neural network models to predict the exchange rate in Sudan through annual exchange rate data between the US dollar and the Sudanese pound. This study aimed to formulate the models of artificial neural networks in which the exchange rate can be predicted in the coming period. The importance of the study is that it is necessary to use modern models to predict instead of other classical models. The study hypothesized that the models of artificial neural networks have a high ability to predict the exchange rate. Use models of artificial neural networks. The most important results ability of artificial neural networks models to predict the exchange rate accurately, Form MLP (1-1-1) is the best model chosen for that purpose. The study recommended the development of the proposed model for long-term forecasting.